UTILIZATION OF PULSE SPRINKLER TECHNIQUE FOR FLAX FIBER EXTRACTION - Tarek Mahmoud ATTAFY; Mohamed Ali EBIED (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study was performed to assess flax fiber extraction by pulse sprinkler technique compared with traditional method (submerged). For this purpose, an experiment was performed in fiber crops research department, Gemmiza Research Station, Gharbeiah Governorate, middle of the Nile Delta, Egypt during September and October, 2019. The micro-sprinkler system was applied with four values of pulses at cycle ratio of ½ namely (one, two, three and four) under two fiber extraction environment conditions (open field and in greenhouse) and two flax varieties Sakha 3 and Giza 12 were applied. The results showed that fiber extraction by TG treatments saved applied water and increased fiber yield rate, fiber length and water productivity comparing with TF treatments and TW. TF4 and TG4 saved applied water comparing with TW by about 17.2 and 25.2 % respectively for Sakha 3 and by about 28.7 and 34.5 % for Giza 12. TW increased fiber yield rate more than TF4 for two varieties Sakha 3 and Giza 12 by 2.6 and 5.3 % respectively, while decreased fiber yield rate less than TG4 by 2.9 and 6.0 % for two varieties respectively. The highest fiber length achieved by TW and TG4 with value of 90.0 cm for variety Sakha 3 and by TG4 with value of 87.0 cm for variety Giza 12. TG4 had the highest water productivity with values of 27.5 and 21.2 kg/m3 for two varieties Sakha 3 and Giza 12 respectively.